Microbial community from arid desert oilfield in response to accurate bio-stimulation remediation. (1st February 2019) - Yu, Wenhe; Chen, Hongkun; Song, Jiayu; Zhao, Chaocheng; Du, Xianyuan; Guo, Chunsheng; Song, Quanwei
Abstract: This research uses Illumina high-throughput sequencing method showing that dominant phylum of dried oily wastewater reservoirs (DOWRs) in oilfield were Proteobacteria, Actinobacteria, Bacteroidetes, and Carbohydrate Metabolism presented a major proportion of metabolic activity. Core microorganism analysis showed that Mycobacterium, Altererythrobacter, Dietzia, Pseudoxanthomonas, Melioribacter were the key genus, which were important in maintaining the microbial construction and function, and which can be treated as the key bio-stimulation community.